The impact of corporate governance on firm value: Evidence from listed manufacturing companies in Sri Lanka - Nayomi Wijesinghe, K.D.G.; Saman Bandara, R.M.; Dassanayake, W.; Undugoda, M.C. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
Good corporate governance is directly linked with the shareholder wealth creation and thereby influence the overall economic prosperity of entities. Firm value is regarded as one of the indicators for the creation of a wealth of an entity. Hence, the purpose of this study is to examine how corporate governance practices impact on the firm value. Data was collected through reviewing the annual reports of 27 Sri Lankan manufacturing firms listed on the Colombo Stock Exchange from 2012 to 2016. The study used descriptive statistics and multiple regression analysis to analyze data. Findings revealed that the number of board meetings of listed manufacturing companies capable of improving firm value. Further, we identified that the control and risk management system of manufacturing entities positively impact firm value while board size and the board committees do not contribute significantly to improve the firm value of manufacturing sector entities in Sri Lanka. The study has social and policy impact as it highlights the importance of corporate governance practices on improving the firm value of the Sri Lankan manufacturing sector. Focusing on one industry sector is an inherent limitation of the study, and industry sector comparison would be a potential future research area.
Keywords: corporate governance; firm value; manufacturing sector; Sri Lanka